Current knowledge of burn injury first aid practices and applied traditional remedies: a nationwide survey. Issue 1 (2nd November 2016) - Kattan, Abdullah E.; AlShomer, Feras; Alhujayri, Abdulaziz K.; Addar, Abdullah; Aljerian, Albaraa
Abstract: Background: Burn first aid awareness has been shown to reduce morbidity and mortality. We present a report on the knowledge and practices of the Saudi population with regard to burn first aid and the application of traditional remedies. Methods: An internet-based survey was conducted to assess the public's knowledge on first aid practices and home remedies applied for burn injuries among Saudi adults. Results: A total of 2758 individuals responded to the survey. There were 1178 (42.7 %) respondents who had previously received burn first aid information. One thousand five hundred fifty respondents had a history of burn exposure in which burn injury first aid was applied as follows: 1118 (72.1 %) removed clothing and accessories from the injured area; water was applied by 990 (63.9 %); among those who applied water, 877 (88.6 %) applied cold water; and only 57 (5.8 %) did so for more than 15 min. Wrapping the burn area was performed by 526 (33.9 %), and 985 (63.5 %) sought medical assistance. When it comes to traditional remedies, 2134 (77.4 %) knew of and/or implemented these remedies as first aid or to treat burns. Honey and toothpaste were the commonest among these remedies with 1491 (69.9 %) and 1147 (53.7 %), respectively. This was associated with female gender ( r  = 0.87, P  < 0.001), younger age group (19–25 years) ( r  = 0.077, P  < 0.001), from central region ( r  = 0.012, P  < 0.001), and university graduate ( r  = 0.05, P  = 0.002). Nearly half of those who knew of traditional remedies did not have previous knowledge of burn first aid. Conclusions: Proper burn first aid is a simple, cheap, and accessible means of managing burns initially. Although the majority of the respondents were university graduates (51.1 %), knowledge and implementation of burn first aid was very poor. Major healthcare agencies should review and promote a consistent guideline for burn first aid in an effort to tackle and minimize the effect of this grave injury.